Heavy metal accumulation capacity of Axinella damicornis (Esper, 1794) (Porifera, Demospongiae): a tool for bioremediation of polluted seawaters - GRAVINA, MARIA FLAVIA; LONGO, CATERINA; PUTHOD, PATRIZIA; ROSATI, MODESTO; COLOZZA, NOEMI; SCARSELLI, MANUELA (Mediterranean Marine Science, 2022)
A wide range of contaminants are continuously introduced into the aquatic environment and among these, heavy metals constitute one of the most dangerous groups because of their persistent nature, toxicity, tendency to accumulate in organisms and more still, they are non-degradable. Marine organisms such as sponges represent target species for the monitoring of heavy metal contamination due their filtering activity. This study aims to evaluate the retention capacity of lead and cadmium by the sponge Axinella damicornis under laboratory conditions. The sponges were exposed for 144 h to seawaters artificially polluted with lead (Pb) and cadmium (Cd) separately and with a mixture of the two metals. The final goal of the experiments was to evaluate the metal uptake in the sponge body and efficiency of the sponge in removing the metals from seawater. In particular, the highest values of metal concentration in the sponges were recorded for Pb: this metal was found to be 6 times and 9 times more concentrated than Cd, respectively in the case of exposure to the single metal and to the combination of both metals. The metal concentrations found, especially for Pb, were much higher in A. damicornis than in other organisms investigated in the sea. Remarkable signs of stress and necrosis were recorded in the specimens when exposed to the combination of Pb and Cd, evidencing a synergistic effect of the metals mixture. This study paves adds knowledge on the contamination effects by heavy metals on the marine organisms and on the contribution from A. damicornis as efficient tool for bioremediation of polluted seawaters.